The vanishing coin - Egan, Kate; Lane, Mike (Egan, Kate. Magic shop., 2014)
Mike reluctantly bonds with good-girl neighbor Nora while learning fun skills at The White Rabbit magic shop, the owner of which believes Mike could become a great magician.